An Ultrasonic Microrobot Enabling Ultrafast Bidirectional Navigation in Confined Tubular Environments - Meng Cui; Liyun Zhen; Xingyu Bai; Lihan Yu; Xuhao Chen; Jingquan Liu; Qingkun Liu; Bin Yang (Nano-Micro Letters, 2025)
Highlights An ultrasonic microrobot achieves bidirectional high-speed locomotion (81 cm s−1) in micro-pipes via frequency modulation. MEMS-fabricated ultrathin piezoelectric composite film enables rapid navigation within confined pipeline (4 mm height), slope climbing (24.25°), and notable load-carrying (>36 times its weight). The microrobot demonstrates agile locomotion across curved pipes, pipes made of various materials, and even over water; integrated micro-endoscope camera enables real-time imaging, highlighting great potential for efficient pipeline inspection.